Is The Natural Order of Morpheme Acquisition Being Appropriately Presented In English Language Teaching Course Books? - David D. Perrodin; Narumon Somboon (JEELS (Journal of English Education and Linguistics Studies), 2019)
This study sought to determine the sequence of L2 morpheme presentation, as well as to determine whether or not the sequence of morpheme presentations correspond with the recognized natural order of morpheme acquisition in English Language Teaching course books utilized with young adult learners at a public sector vocational education institution in Thailand. Qualitative analysis was employed in the scrutinizing of twelve beginner and elementary level ESL and EFL learners course books that have been utilized as the primary teaching material for over a decade by the general education department of the institute. This examination revealed that the morpheme presentation sequence within the selected ELT course books was not analogous with the conclusions in the supporting literature. The findings further indicated that the widely accepted viewpoint of natural order morpheme acquisition was likewise not substantially reflected within the analyzed texts. Albeit, earlier studies have found that an unnatural sequence of morpheme presentation in EFL course books may hamper communicative competence in English, further study is required to establish if this may be a contributing factor for the overall low English proficiency of adult L2 learners in Thailand.